Nutritional Content and Bioactive Compounds of Banana Peel and Its Potential Utilization: A Review - Muhammad Ansari , Nur Anis Insyirah; Ramly, Nurzazarina; Faujan , Nur Huda; Arifin, Norlelawati (Malaysian Journal of Science Health & Technology, 2023)
Banana is one of the popular fruits among consumers due to their excellent nutritional value. However, banana peel, the fruit’s main secondary product or a significant by-product in banana processing, is generally abandoned and discarded as waste. Banana peels are rich in nutritional content such as protein, carbohydrates, fat, moisture, and ash contents. They are also high in bioactive compounds such as phenolic (flavonoids) and various types of carotenoids (lutein, alpha-carotene, and beta-carotene). Phenolic compounds effectively protect the human body against various diseases, specifically oxidative stress-related diseases. Due to all the advantages of banana peels, plenty of potential utilization could be explored, including citric acid production by Aspergillus niger, traditional medicine, foods, and pharmaceutical industries, as well as dietary incorporation. Thus, this paper discussed the nutritional contents and bioactive compounds of banana peel and their potential utilization as food additives, supplements, and pharmaceuticals. This could then help to minimize the number of agro-solid waste disposal from the food industry by processing the waste into value-added products.